2014
DOI: 10.1016/j.yhbeh.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol rapidly facilitates lordosis through G protein-coupled estrogen receptor 1 (GPER) via deactivation of medial preoptic nucleus μ-opioid receptors in estradiol primed female rats

Abstract: In female rats sexual receptivity (lordosis) can be induced with either a single large dose of estradiol benzoate (EB), or a priming dose of EB that does not induce sexual receptivity followed by 17β-estradiol (E2). Estradiol priming initially inhibits lordosis through a multi-synaptic circuit originating in the arcuate nucleus of the hypothalamus (ARH) that activates and internalizes μ-opioid receptors (MOR) in medial preoptic nucleus (MPN) neurons. Lordosis is facilitated when MPN MOR are deactivated after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…Like EB-only, we have also found that facilitation of lordosis by the EB + non-esterfied-estradiol requires the activation of ORL-1 (Long et al, 2013(Long et al, , 2014. If EB-primed nonreceptive rats are infused with UFP-101 prior to the non-esterfied-estradiol infusion, then MPN MOP remain activated and sexual receptivity is not facilitated (Long et al, 2013(Long et al, , 2014.…”
Section: Ofq/n-orl-1 Regulation Of Sexual Receptivitymentioning
confidence: 97%
See 4 more Smart Citations
“…Like EB-only, we have also found that facilitation of lordosis by the EB + non-esterfied-estradiol requires the activation of ORL-1 (Long et al, 2013(Long et al, , 2014. If EB-primed nonreceptive rats are infused with UFP-101 prior to the non-esterfied-estradiol infusion, then MPN MOP remain activated and sexual receptivity is not facilitated (Long et al, 2013(Long et al, , 2014.…”
Section: Ofq/n-orl-1 Regulation Of Sexual Receptivitymentioning
confidence: 97%
“…The onset of sexual receptivity in estradiol-only treated animals is delayed and begins about 48 h after initial estradiol treatment, whereas progesterone can facilitate lordosis if given as early as 20-24 h after EB priming (Boling & Blandau, 1939;Sinchak & Micevych, 2001). A third, less used steroid priming paradigm that also induces maximal levels of sexual receptivity primes first with 2 μg EB followed by 17β-estradiol not conjugated to a benzoate molecule (non-esterfied-estradiol) in the place of progesterone (Long, Serey, Welborn, & Sinchak, 2013;Long, Serey, & Sinchak, 2014;Parsons, Rainbow, Snyder, & McEwen, 1984;Pfaff, Schwartz-Giblin, McCarthy, & Kow, 1994). Interestingly, in this last paradigm, lordosis is facilitated within 30 min of non-esterfied-estradiol treatment, and this nonesterfied-estradiol has been shown to be activating an extranuclear estrogen receptor (ER), G protein-coupled estrogen receptor-1 (GPR30; aka GPER-1; Fig.…”
Section: Reproductive Behaviormentioning
confidence: 99%
See 3 more Smart Citations